Multi-group modeling of protection against neutron and gamma radiation by materials based on titanium hydride - Yastrebinsky, R.N.; Karnaukhov, A.A. (Вопросы атомной науки и техники, 2020)
The paper provides a comparative calculation of the radiation protective efficiency of various composite materials based on titanium hydride using multi-group modeling methods using the ANISN program. The calculations showed the high efficiency of titanium hydride composites with respect to neutron and gamma radiation. The relaxation length of the fast neutron flux density in titanium hydride materials is 5.1…7.0 cm. The spatial-energy distribution of neutron radiation in materials is formed by fast neutrons. The dose rate of gamma rays behind the material is determined mainly by capturing gamma rays arising in the initial layer of protection. Introduction to the composition of the protection of boron atoms reduces the level of capture gamma radiation, but does not affect the attenuation of fast neutrons.